Software and Tools in Online Chemistry Class and Experimental Activities During Covid-19 Pandemic: A Systematic Literature Review - Nathasya Imanuella; I Wayan Redhana (Jurnal Penelitian Pendidikan IPA, 2023)
The COVID-19 outbreak had transformed the chemistry learning from physical class to online class. The alteration in class method could be challenging for several instructors, particularly those who were not aided with technological advancements and adequate training. One of the challenges was the selection of software and tools used in online lectures as well as online experiments class. Herein, we present a systematic literature review with the PRISMA model from two databases regarding the software and tools many researchers used in chemistry learning during COVID-19 pandemic. The particular steps of laboratory activities and students’ perspectives towards these learning tools were also incorporated in the results and discussion. At the end of the review, we provide the promising directions of learning tools for future chemistry learning too